Model CORE (Connecting, Organizing, Reflecting, Extending) pada Pembelajaran Matematika Sekolah - Ulya, Khairatul; Srimuliati, Srimuliati; Husna, Raudatul; Anggreini, Rindu; Zaiyar, M. (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2024)
The CORE model is known as a learning model that emphasizes students' thinking skills. Students' abilities are developed through the stages of connecting, organizing, exploring, and managing information obtained before, during and after learning. This model will help students in connecting between materials so that learning is more meaningful. This study aims to determine how the CORE model is in mathematics learning in schools. The population taken was all students of class X MAN 1 Aceh Tamiang. Using the simple random sampling technique, class 1A students acted as research samples. Data collection techniques were carried out using observation techniques, questionnaires and also learning outcome tests. Based on the results of the study, it showed that, (1) the results of observations of teachers' abilities in managing learning using the CORE model were given the predicate of being implemented well, (2) the results of observations of student activities towards learning using the CORE model were given the predicate of being very good, (3) students' responses to CORE learning were positive, (4) and the results of the student learning completion test after learning with the CORE model were complete.